Pengaruh Functional Training Terhadap Kapasitas Otot Lengan, Torso dan Tungkai pada Atlet Tolak Peluru - Ardiansyah Ardiansyah; A. Rusdiana; D. Budiana; Y. Sunaryadi; Sucipto Sucipto; D. F. Anggara (Universitas Hamzanwadi, 2025)
Shot put is a sport that relies on explosive strength and energy transfer through the kinetic chain. However, conventional training approaches that focus on isolated muscle strengthening are often ineffective because they do not resemble the multidimensional movement patterns seen in competition. This study aims to analyze the effect of a functional training program on increasing lean muscle mass in the arms, torso, and legs of shot put athletes. The method used was a quasi-experiment with a one-group pre-test post-test design. A total of 16 male athletes participated in a structured functional training program for 8 weeks with a frequency of 3 sessions per week. Lean muscle mass was measured using Bioelectrical Impedance Analysis (BIA) with a strict protocol. Data were analyzed using a paired sample t-test and Cohen's d. The results showed a significant increase in lean muscle mass in all three areas: arms increased by 1.36% (p < 0.001; d = 3.111), torso by 0.60% (p < 0.001; d = 3.361), and legs by 0.68% (p < 0.001; d = 3.525). The highest absolute increase occurred in the torso (0.192 kg). The conclusion of this study is that a periodization-based functional training program effectively increases lean muscle mass significantly in shot put athletes, with a very large practical impact (large effect size).